The Need for Integrative Computational Oncology: An Illustrated Example through MMP-Mediated Tissue Degradation - Mumenthaler, Shannon; D'Antonio, Gianluca; Preziosi, Luigi; Macklin, Paul (Frontiers in Oncology, 2013)
Physical oncology is a growing force in cancer research, and it is enhanced by integrative computational oncology: the fusion of novel experiments with mathematical and computational modeling. Computational models must be assessed with accurate numerical methods on correctly-scaled tissues to avoid numerical artifacts that can cloud analysis. Simulation-driven analyses can only be validated by careful experiments. In this perspectives piece, we evaluate a current, widespread model of matrix metalloproteinase-driven tissue degradation during cancer invasion to illustrate that integrative computational oncology may not realize its fullest potential if either of these critical steps is neglected.